Effect of Paracoccus sp. and their Genetically Modified on Skin Coloration of Red Sea Bream - KURNIA, AGUS; SATOH, SHUICHI; HANZAWA, SATOSHI (HAYATI Journal of Biosciences, 2010)
Astaxanthin (Asx) content in the skin of red sea bream was observed in a feeding trial with two Asx sources: marine bacteria (Paracoccus sp.) and Asx concentrated marine bacteria modified genetically (GM marine bacteria). Four semi purified diets were prepared and contained two levels of marine bacteria (15 and 30 mg Asx/kg), 30 mg Asx/kg of GM marine bacteria and control diet without additional Asx. The diets were fed to fourteen fish of red sea bream (initial weight 128.5 g) which were randomly distributed in each 60-l glass tank. Asx content in the skin of fish fed on non-GM marine bacteria diets were higher than that of fish fed on GM marine bacteria.  Additionally, Asx accumulation in the skin of fish fed on diet of non-GM marine bacteria containing 15 mg Asx/kg diet was higher than those fish fed on diet supplemented with 30 mg Asx/kg of GM marine bacteria. The results showed that by adding the supplement of Asx derived from marine bacteria (Paracoccus sp.) to the red sea bream diets might enhance the skin coloration of red sea bream and the other carotenoids contained in marine bacteria might also enhance the coloration.